The ERK 1 and 2 Pathway in the Nervous System: From Basic Aspects to Possible Clinical Applications in Pain and Visceral Dysfunction - Cruz, Celia D.; Cruz, Francisco (Current Neuropharmacology, 2007)
The extracellular signal-regulated kinases 1 and 2 (ERK) cascade, member of the mitogen-activated protein kinases superfamily of signalling pathways, is one of the best characterized pathways as many protein interactions and phosphorylation events have been systematically studied. Traditionally, ERK are associated with the regulation of proliferation and differentiation as well as survival of various cell types. Their activity is controlled by phosphorylation on specific aminoacidic residues, which is induced by a variety of external cues, including growth-promoting factors. In the nervous system, ERK phosphorylation is induced by binding of neurotrophins to their specific tyrosine kinase receptors or by neuronal activity leading to glutamate release and binding to its ionotropic and metabotropic receptors. Some studies have provided evidence of its importance in neuroplastic events. In particular, ERK phosphorylation in the spinal cord was shown to be nociceptive-specific and its upregulation, occurring in cases of chronic inflammatory and neuropathic pain, seems to be of the utmost importance to behavioural changes observed in those conditions. In fact, experiments using specific inhibitors of ERK phosphorylation have proved that ERK directly contributes to allodynia and hyperalgesia caused by spinal cord injury or chronic pain. Additionally, spinal ERK phosphorylation regulates the micturition reflex in experimental models of bladder inflammation and chronic spinal cord transection. In this review we will address the main findings that suggest that ERK might be a future therapeutic target to treat pain and other complications arising from chronic pain or neuronal injury.
Keywords: ERK inhibition